1982
DOI: 10.1159/000176590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Protein and Lipid on the Activity of Hepatic Mixed-Function Oxidase System in Young and Adult Rats

Abstract: Effects of marginal or normal casein diets with different sunflower oil contents were tested on the hepatic mixed-function oxidase system in young and adult male rats. The weight gain and the activity of aminopyrine demethylase, aniline hydroxylase and the content of cytochrome P-450 was decreased only in young rats fed 10% casein and 10% oil containing diets. Both in young and adult animals, independently of casein consumption, the activity of MFO with the exception of cytochrome P-450 in adult rats fed 20% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Corn oil, olive oil, and sunflower oil supplementation at levels ranging from 0.5 to 30% of total food intake are reported to increase hepatic CYP content and catalytic activity. 7, 11, 17, 18 However, in another study, sunflower oil decreased the total protein content 19. Yoo et al11 reported that rats given 20% corn oil supplement for 4 days had an increase in the 6β‐testosterone hydroxylation, but had no change in 7α‐ and 16α‐testosterone hydroxylation.…”
Section: Discussionmentioning
confidence: 98%
“…Corn oil, olive oil, and sunflower oil supplementation at levels ranging from 0.5 to 30% of total food intake are reported to increase hepatic CYP content and catalytic activity. 7, 11, 17, 18 However, in another study, sunflower oil decreased the total protein content 19. Yoo et al11 reported that rats given 20% corn oil supplement for 4 days had an increase in the 6β‐testosterone hydroxylation, but had no change in 7α‐ and 16α‐testosterone hydroxylation.…”
Section: Discussionmentioning
confidence: 98%
“…However, as shown in Table 3, the increase is at best modest and the minor variation is unlikely to be of any important physiological significance. Concerning the effect of protein quantity on the activity of liver microsomal MFO system, it has been shown so far that diets with lower levels of casein (5-12% by weight) decrease the activities of liver microsomal MFO system as measured by cytochrome P-450, O-deethylase, O-demethylase, N-demethylase and hydroxylase compared with a diet containing a normal level of casein (20% by weight) (2,4,8,9,11,(13)(14)(15). This discrepancy between these and our results appears to depend on protein quality, where casein has limiting amino acids and whole egg protein no limiting amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…SAITO et al normal levels (2,4,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). By contrast, dietary protein excess is reported to increase (11) or decrease (13) the activity of liver microsomal MFO system.…”
mentioning
confidence: 99%
“…In a similar pattern, aniline hydroxylase was in a trend to increase by feeding CO. The MFO system in the liver plays a crucial role in the metabolism of endogenous steroids (TAKAHASHI and JENSEN,1984) and the maintenance and induction of MFO system are optimized by dietary fat in rats (ANTAL et al, 1982).…”
Section: Effects Of Dietary Fat Sourcesmentioning
confidence: 99%